Networked systems : First International Conference, NETYS 2013, Marrakech, Morocco, May 2-4, 2013, Revised Selected Papers - Guerraoui, Rachid; Gramoli, Vincent (Lecture Notes in Computer Science, 2013)
This book constitutes the revised selected papers of the First International Conference on Networked Systems, NETYS 2013, held in Marrakech, Morocco, in May 2013. The 33 papers (17 regular and 16 short papers) presented were carefully reviewed and selected from 74 submissions. They address major topics from theory and practice of networked systems: multi-core architectures, middleware, environments, storage clusters, as well as peer-to-peer, sensor, wireless, and mobile networks.